2012
DOI: 10.1186/ar4056
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, multicenter, placebo-controlled phase III trial to evaluate the efficacy and safety of pregabalin in Japanese patients with fibromyalgia

Abstract: IntroductionFibromyalgia is a chronic disorder characterized by widespread pain and tenderness. Prior trials have demonstrated the efficacy of pregabalin for the relief of fibromyalgia symptoms, and it is approved for the treatment of fibromyalgia in the United States. However, prior to this study, there has not been a large-scale efficacy trial in patients with fibromyalgia in Japan.MethodsThis randomized, double-blind, multicenter, placebo-controlled trial was conducted at 44 centers in Japan to assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 27 publications
(48 reference statements)
12
71
2
2
Order By: Relevance
“…Pregabalin improved diverse FM clinical domains, including severity of anxiety and depression, patient function and global status, and sleep behaviors, consistent with previous studies that used doses of 300 or 450 mg/day 10,12,13,14,16,24,27 . HADS-A and HADS-D scores significantly improved with pregabalin treatment versus placebo.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Pregabalin improved diverse FM clinical domains, including severity of anxiety and depression, patient function and global status, and sleep behaviors, consistent with previous studies that used doses of 300 or 450 mg/day 10,12,13,14,16,24,27 . HADS-A and HADS-D scores significantly improved with pregabalin treatment versus placebo.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the treatment difference was similar to that seen in 5 pivotal studies in patients with FM not receiving concurrent antidepressant medication 10,12,13,14,24 . In those studies, the difference in mean pain score between pregabalin (300 or 450 mg/day) and placebo ranged from -0.33 to -0.98, compared with -0.61 in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Crofford et al found that only 450 mg/day dosing was superior to placebo for pain efficacy (not at 150 or 300 mg/day) 113 . At doses of 300 or 450 mg/day, Ohta et al reported superior efficacy of pregabalin over placebo 114 . Arnold et al 115 and Clair 116 et al also reported superior efficacy of pregabalin in pooled groups of pregabalin doses (300–450 mg/day) over placebo.…”
Section: Findings From Studies Grouped By Chronic Pain Syndromementioning
confidence: 99%
“…Currently, pregabalin is indicated for the management of neuropathic pain associated with diabetic peripheral neuropathy (8,9), postherpetic neuralgia (10,11), and management of fi bromyalgia (12,13). In addition, pregabalin is used frequently in the treatment of anxiety (14).…”
Section: Introductionmentioning
confidence: 99%